The Impact of Coordination Between Nursing and Patient Care Technicians on Reducing Critical Errors in Intensive Care Units - Alhuzli, Seham Mutlq; Alshomrani, Mohammed Hamed; Alasmari, Khadijah Hasan; Etuoody, Reema Ali; Najmi, Yahya Ahmed; Alwadai, Abdulaziz Mohammed Saleh; Almani, Ali Yahay Ali; Al Shabi, Safya Abdulla Mohammad; Hakami, Zohoor Jaber Ali; Hamadi, Fatmah Abdu Ibrahim; Faqehi, Tasneem Shaker (Journal of Posthumanism, 2024)
The Intensive Care Unit (ICU) represents a nexus of high-acuity patient care, advanced technology, and profound human vulnerability, creating an environment where the potential for critical error is exceptionally high. This research paper posits that effective, structured coordination between Registered Nurses (RNs) and Patient Care Technicians (PCTs) is a critical, yet often under-examined, determinant of patient safety within this complex setting. The analysis explores the ICU as a complex adaptive system, where linear, mechanistic approaches to safety are insufficient. It meticulously delineates the distinct, yet interdependent, roles of the ICU RN, who holds responsibility for clinical assessment and care coordination, and the PCT, who provides essential direct patient support and frontline data collection. The fundamental mechanisms of coordination failure are examined, including communication breakdowns rooted in hierarchical barriers and divergent care priorities, as well as flawed delegation practices that violate established professional standards. The paper synthesizes evidence from peer-reviewed literature and authoritative reports from organizations such as the World Health Organization (WHO), the American Association of Critical-Care Nurses (AACN), and the Institute for Healthcare Improvement (IHI) to identify evidence-based strategies that mitigate these risks. These strategies include the implementation of structured communication protocols like SBAR, the cultivation of a psychologically safe environment, and the use of interprofessional simulation-based training. The paper concludes by presenting a multi-level set of recommendations for healthcare organizations, unit-level leaders, and frontline clinicians, arguing that cultivating a high-reliability Nurse-PCT dyad is an indispensable component of any comprehensive patient safety program.